Shear forces transfer in steel-concrete slim floor with circular web opening and PCHCS. (April 2022) - Coldebella, Gustavo; Ferreira, Felipe Piana Vendramell; De Nardin, Silvana
Abstract: An experimental study was developed to investigate the mechanisms responsible for the transfer of shear forces at the steel-concrete interface in slim floor beams with circular web openings and precast hollow core slab (PCHCS). For this purpose, four specimens were made and subjected to push-out test. The presence of the steel bar through the opening, the concrete compressive strength and the diameter of the steel bar were studied. It was observed that the presence of the steel bar contributed significantly to both the resistance of the connection and for the reduction of the relative slip values of steel-concrete. While the specimen without steel bar presented a post-peak behavior with a drop of resistant capacity, in the specimens with steel bar the load-slip relationship was quite ductile. The variation in steel bar diameter and concrete strength influenced both load-slip relationship and resistant capacity. It was observed that regardless of the presence of steel bar, until the concrete dowel rupture, the load-slip behavior of the specimens with and without steel bar was almost identical. The experimental results were compared to analytical models proposed by other researchers. However, none of the analytical models found in the literature were able to satisfactorily represent the resistant capacity of the specimens with and without steel bar. A good estimate of the theoretical results was obtained using the friction-shear theory for concrete corbels.